Local government innovation model in Pekanbaru City, Indonesia: a study of public service mall - Ranggi Ade Febrian; Khairul Rahman; Ahmad Fitra Yuza; Zainal Zainal (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
This research aims to find a model for implementing local government innovation in Pekanbaru City. One of the Innovation Public Service Mall innovations with the highest score is SMART PETAKU (Pekanbaru City Government Land Asset Management System) with a score of 820. However, there are still several innovations with the lowest score, one of which is the E-Archive with a score of 0. Using the theory of disruptive innovation ( Yu Hang, 2010), the basic design of this study uses a qualitative method with a descriptive approach from primary data sources obtained from in-depth interview techniques and secondary data, namely passive observation techniques. The research findings show that first, the success of the internal perspective is determined by the indicators of visionary and innovative local government head leadership, the right organizational structure with the establishment of a Public Service Mall, an organizational culture that is not separated from the pathology of democracy, and employee competencies that require development. Second, an external perspective determined by supervision from the Pekanbaru City DPRD, community participation, and appreciation factors that have a significant effect on the performance of the Pekanbaru City Government. Third, the marketing aspect is supported by the existence of a dynamic website from the content and information presented. Fourth is the technological perspective, where the Pekanbaru City Government through the Public Service Mall applies the E-Gov concept with application designs for requests and complaints. The conclusion of the study found the IEMT model with internal, external, market, and technology perspective dimensions. Recommendations for further research are collaborative governance studies in service innovation with the private sector at Public Service Malls which are still disproportionate.